2008
DOI: 10.1111/j.1945-5100.2008.tb00642.x
|View full text |Cite
|
Sign up to set email alerts
|

Archaeabacterial lipids in drill core samples from the Bosumtwi impact structure, Ghana

Abstract: Abstract-Meteorite impacts are associated with locally profound effects for microorganisms living at the terrestrial surface and the subsurface of the impact zone. The Bosumtwi crater in Ghana (West Africa) is a relatively young (1.07 Myr) structure with a rim-to-rim diameter of about 10.5 km. In a preliminary study targeting the subsurface microbial life in the impact structure, seven samples of the impact breccia from the central uplift of the Bosumtwi crater were analyzed for the presence of typical archaea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Other studies resulting from the ICDP drilling project include a search for biological activity in the form of archaeal membrane-lipids, which were detected in impactite core samples and might be related to the soils or rocks predating the impact event, the hydrothermal system generated after the impact, or due to more recent underground water transport ( Escala et al, 2008 ). The cosmogenic radionuclide Be-10 was used to investigate as to whether surface-derived material is present in the suevitic breccia within the drill core of the Bosumtwi crater so that the extent of mixing of target rocks during crater formation in respect to the fallback breccia can be determined; it was found that only a small number of clasts in the suevite was derived from near the target surface, indicating that in-crater breccias were well mixed during the impact cratering process ( Losiak et al, 2014 ).…”
Section: The Impact Record Of Africamentioning
confidence: 99%
“…Other studies resulting from the ICDP drilling project include a search for biological activity in the form of archaeal membrane-lipids, which were detected in impactite core samples and might be related to the soils or rocks predating the impact event, the hydrothermal system generated after the impact, or due to more recent underground water transport ( Escala et al, 2008 ). The cosmogenic radionuclide Be-10 was used to investigate as to whether surface-derived material is present in the suevitic breccia within the drill core of the Bosumtwi crater so that the extent of mixing of target rocks during crater formation in respect to the fallback breccia can be determined; it was found that only a small number of clasts in the suevite was derived from near the target surface, indicating that in-crater breccias were well mixed during the impact cratering process ( Losiak et al, 2014 ).…”
Section: The Impact Record Of Africamentioning
confidence: 99%
“…Colonization of the subsurface breccia is reported in the 1.07 Ma Bosumtwi impact structure in which archaeal lipids have been detected (Escala et al, 2008). The authors proposed three possible sources of the lipids.…”
Section: Impact Fracturingmentioning
confidence: 97%